"Phacing" a New Cause of Carotid Artery Dissection. Issue 2 (March 2017) - Kulyk, Caterina; Farina, Filippo; Palmieri, Anna; Viaro, Federica; Causin, Francesco; Laverda, Anna M.; Baracchini, Claudio
Abstract : Introduction: Cervical arterial dissection (CAD) is a frequent and preventable cause of ischemic stroke in young patients. Several arguments suggest that genetic and developmental disorders could play an important role as part of a multifactorial predisposition of sporadic CAD. We present 2 cases of young patients with CAD in association with cutaneous lesions and nonatherosclerotic multivessel arteriopathy. Case Reports: Our first patient was a 17-year-old white girl with sudden onset of weakness in her right upper limb. A magnetic resonance angiogram showed a severe stenosis along the extracranial and intracranial segments of the left internal carotid artery and the left middle cerebral artery. A complete ultrasound study confirmed the stenoses with characteristics suggestive of dissection. Our second patient was a 7-year old white girl with a past history of left middle cerebral artery ischemic stroke. During the follow-up, an ultrasonographical examination discovered an asymptomatic dissection of the right internal carotid artery. Both patients reported a history of large unilateral hemangiomas; in the first case a coloboma of the left optic disc and an aortic aneurysm were also present. These findings were suggestive of PHACE—a neurocutaneous developmental syndrome associated with constitutional arteriopathy of the major cerebral vessels. Conclusions: Noteworthy, among vascular abnormalities of PHACE, CADs have never been reported before. Our 2 cases suggest that CAD is an underecognized cerebrovascular manifestation of PHACE and it should be searched for in these patients. Ultrasound, being noninvasive and portable, is a useful tool for the assessment and follow-up of these patients.